The Impact of Wind Movement on Providing Thermal Comfort in Urban Design - Musa, Hala Hussein; Asadi, Fawzia; Majeed, Anas Hameed (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
The wind movement is a crucial factor in enhancing thermal comfort, forming an essential part towards friendly and sustainable urban environment. Air movement, as a prominent climatic factor, reduces heat stress with improving ventilation quality. Effective natural ventilation and heat stress mitigation can be achieved by orientation, planning and shaping the urban blocks in urban environments. Air movement represents the most important element in improving environmental adaptation, as the rapid airflow reaching buildings can significantly reduce their temperature. Site planning requires precise knowledge of the main wind directions and speeds. The research utilized the ENVI-met Models program for modeling urban environments and predicting thermal effects in the built environment. This program plays a crucial role in understanding and analyzing environmental conditions and their impact on thermal comfort. The research addressed the knowledge gap and lack of local studies in highlighting the role of wind movement in enhancing thermal comfort in urban environments using ENVI-met Models. The research aimed to provide specific knowledge in measuring wind movement and its role in enhancing thermal comfort in urban environments using the program. The research hypothesized that analyzing and modeling wind movement with ENVI-met Models can effectively contribute to understanding and improving thermal comfort in urban environments. One of the key findings is that studying the impact of wind movement with this program is essential for providing scientific and technical foundations to improve urban design and enhance thermal comfort in urban areas, promoting sustainability and environmental quality in cities